Analisis Tingkat Kesiapan Pengguna Sistem Informasi Koreksi Essay Otomatis Berbasis Web Menggunakan Model Technology Readiness Index (TRI) - Rifki Adhitama; Aditya Wijayanto; Dwi Mustika Kusumawardani (JSINBIS (Jurnal Sistem Informasi Bisnis), 2021)
During the pandemic, the learning model directly impacts both students and teachers, especially in evaluating and correcting assignments to measure student learning. Evaluation and correction of the learning process at both the high school and high school and university levels are generally carried out multiple-choice examinations during this pandemic. Many tools can be used to carry out multiple-choice assessments. The essay assessment is usually done manually and takes a long time because the lecturer has to make corrections one by one. On the other hand, information retrieval is a concept that can be used to build an automatic essay correction information system so that the correction of essay questions can be done quickly and efficiently, as in multiple-choice works. The automatic essay correction information system is a relatively new technology, especially for its plural use in this pandemic. A new technology that will be applied in a plural manner requires a measurement. One of the measurements that can be used is the Technology Readiness Index (TRI). TRI is used because it can measure the readiness and tendency of users to implement an information system. The case study in this research was conducted at the Faculty of Informatics (FIF) Telkom Institute of Technology Purwokerto (ITTP). The TRI measurement of the automatic essay correction information system carried out at FIF produces a TRI of 3.27. This value is between 2.90 and 3.51 (2.90 ≤ TRI ≤ 3.51). Consisted of an optimism value of 1.01, and innovativeness value of 0.52, a discomfort value of 0.55, and an insecurity value of 1.19.